Implementasi Project Based Learning Melalui Pohon Qurma Pada Mata Pelajaran Qurma - Wahyuni Ahadiyah; Nicky Estu Putu Muchtar; Lusia Mumtahana (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2022)
The lagging behind in the world of education in Indonesia is due to the slow adjustment to the progress of the times, namely that there are still many teachers who use the Teacher-Centered Learning approach. So it is necessary to evolve using the Student-Centered Learning approach. MI Narrative Quran has a unique curriculum contained in Mulok QURMA (Quran and Meaning). Student projects as learning outcomes as a form of student-centered learning development. Does this study aim to find out how to apply the Project Based Learning learning model through the QURMA TREE in the QURMA subject at MI Narrative Quran Lamongan? And what are the supporting factors and obstacles in implementing PBL through the QURMA TREE at MI Narrative Quran Lamongan? This type of research is qualitative with a descriptive approach. Data collection was carried out using observation, interview, and documentation methods. The subjects of this study were students, teachers, and school principals. The data analysis methods in this study are data collection, data reduction, data presentation, data triangulation, and conclusion. MI Narrative Quran Lamongan madrasah wants to always prioritize the Koran by innovating to develop MULOK QURMA learning. The QURMA TREE is the product of each class which is carried out once every three months as an implementation of the Project Based Learning learning model in the QURMA mulok subject (Quran and Meaning). The QURMA TREE at MINAN is teaching materials compiled by the QURMA team, namely the preparation of the QURMA MUSHAF for grades 1 to grade 6, a special and coordinated teaching team consisting of 6 people, excellent programs as well as the tahfidz program as a pillar of the madrasa, namely tahfidz, QURMA, and language, adequate facilities and means, clearly and continuously scheduled program of events. The obstacles can be summarized as follows: the conditioning of the students as audiences, the duration or timing of the implementation, which is not following the plan rundown, and the place where the organizers are less supportive during rainy weather because it is held outdoors.